What shapes students' perceptions of group work: personality or past experience?. Issue 9 (20th July 2020) - Elmassah, Suzanna; Mostafa Bacheer, Shereen; James, Reynold
Abstract : Purpose: Group work (GW) as a collaborative learning method for university students is a much-researched topic in the literature. However, a fairly neglected area is that of students' perceptions of the same. This study purports to bridge this gap in the extant literature via identifying the determinants of these perceptions. Design/methodology/approach: Using primary data gathered from a sample of 443 university students, the study applies the structural equation modeling (SEM) to estimate the impact of both personal traits and past experiences on the students' perceptions. Findings: The SEM results reveal that students' perceptions of GW are determined by their relevant past experiences not by their personalities. This position is contradictory to other relevant studies undertaken thus far. Practical implications: Accordingly, the study stresses the need for educators to create positive group experiences among students and to convert their past negative experiences into positive ones. Originality/value: Whilst group work holds significant learning benefits for students, negative perceptions about this rich method could eventuate in students refraining from participating in the same. By isolating the determinants associated with students' negative perceptions of GW, this study provides educationists with a strong case for developing suitable interventions aimed at enhancing students' positive perceptions of GW, and resultantly further maximizing its potential benefits.